u= ln(sqrt(x^2+y^2))

u(x) = x / (2sqrt((x^2+y^2))

u(xx) = (1-2x^2)/(2(sqrt(x^2+Y^2))^3)

u(y)= y / (2sqrt((x^2+y^2))

u(yy)= (1-2y^2)/(2(sqrt(x^2+Y^2))^3)

i havent done derivatives for a while now (Doh).. not sure it is correct..

Printable View

- Oct 6th 2008, 10:35 PMmathlovetneed my work checked plz :)
u= ln(sqrt(x^2+y^2))

u(x) = x / (2sqrt((x^2+y^2))

u(xx) = (1-2x^2)/(2(sqrt(x^2+Y^2))^3)

u(y)= y / (2sqrt((x^2+y^2))

u(yy)= (1-2y^2)/(2(sqrt(x^2+Y^2))^3)

i havent done derivatives for a while now (Doh).. not sure it is correct.. - Oct 6th 2008, 11:11 PMlllll
you could use some of the properties of logarithms for this one:

so then: